Notes on Jerzy Grotowski and Maud Robart’s Researches on Afro-diasporic Chants - Matricardi, Luciano (Revista Brasileira de Estudos da Presença, 2023)
This paper discusses the transcultural investigations conducted by Jerzy Grotowski on traditional AfroDiasporic chants. Based on some notes on the collaboration with the Haitian artist Maud Robart, it argues that these investigations were not aimed at the expropriation of traditional performative knowledge, the emptying of its meanings or the aestheticization of its forms. In its political dimension, as it seeks to delineate, it was a work that had the potential to relativize the usual modes of perception of the individual, especially the modern and western one, towards what could be called a ‘decolonization of the self’.